2011
DOI: 10.1016/j.freeradbiomed.2011.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Long-term intermittent feeding, but not caloric restriction, leads to redox imbalance, insulin receptor nitration, and glucose intolerance

Abstract: Calorie restriction is a dietary intervention known to improve redox state, glucose tolerance, and animal life span. Other interventions have been adopted as study models for caloric restriction, including nonsupplemented food restriction and intermittent, every-other-day feedings. We compared the short- and long-term effects of these interventions to ad libitum protocols and found that, although all restricted diets decrease body weight, intermittent feeding did not decrease intra-abdominal adiposity. Short-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 44 publications
2
46
0
6
Order By: Relevance
“…Understanding metabolic differences between dieting approaches is nonetheless important as it may identify potential applications of IER within certain patient subgroups. Rodent studies (examining glycaemic indices) have demonstrated comparable short-term outcomes between IER and CER (8,15,17) , but also worse longer-term outcomes with IER (15) , which is discussed further in the following section. Considering the rodent literature in its entirety, a large proportion of studies have reported a lack of full energy compensation on feed days, irrespective of background diet composition (9,10,13,(16)(17)(18)(19) .…”
Section: Outstanding Questionsmentioning
confidence: 92%
See 1 more Smart Citation
“…Understanding metabolic differences between dieting approaches is nonetheless important as it may identify potential applications of IER within certain patient subgroups. Rodent studies (examining glycaemic indices) have demonstrated comparable short-term outcomes between IER and CER (8,15,17) , but also worse longer-term outcomes with IER (15) , which is discussed further in the following section. Considering the rodent literature in its entirety, a large proportion of studies have reported a lack of full energy compensation on feed days, irrespective of background diet composition (9,10,13,(16)(17)(18)(19) .…”
Section: Outstanding Questionsmentioning
confidence: 92%
“…The majority of rodent studies (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) and a small number of human studies (22)(23)(24)(25)(26) have used IER protocols, which completely restrict energy intake (i.e. 100 % energy restriction) every other day, with fasting intervals ranging between 20 and 36 h. However, the long-term sustainability of this alternate day total fasting approach in human subjects is questionable due to the persistent hunger reported (24) .…”
Section: Overview and Effects On Body Weightmentioning
confidence: 99%
“…[51][52][53] Another large body of work demonstrates that ROS release from mitochondria or tissues from CR animals is decreased. 37,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67] Other publications found no changes in ROS production with CR 46,[68][69][70][71] and many propose that CR-induced decreases in ROS release depend on tissues examined, time on the diet, animal age when the diet was initiated, and gender. No experimental publication was located demonstrating that CR in rodents enhances ROS generation in non-inflammatory tissues.…”
Section: Effects Of Cr On Redox State In Vertebratesmentioning
confidence: 99%
“…10 Many of these diets are in fact the restriction of total food, incurring malnutrition, and may lead to a loss of tissue antioxidant capacity. 67 Other researchers have adopted intermittent or every other day feedings as 'caloric restriction' protocols. 72 We recently found that this feeding pattern very significantly increases ROS release from skeletal muscle and adipose tissue, while CR prevents this release.…”
Section: Effects Of Cr On Redox State In Vertebratesmentioning
confidence: 99%
See 1 more Smart Citation